The number of emergency department visits for psychiatric emergencies is strongly associated with mean temperature and humidity variations. Results of a nine year survey - Gianfranco Cervellin (Emergency Care Journal, 2014)
Several disorders, such as renal colics, stroke, atrial fibrillation and others, are epidemiologically associated with seasonality and microclimatic variations. Although evidence is still limited, an association between psychiatric emergencies and seasonality has also been previously described. In order to elucidate the possible association between weather and incidence of psychiatric emergencies in a country with temperate climate, we analyzed the influence of day by day climate changes on the number of visits for psychiatric emergencies in an urban emergency department (ED) of northern Italy. All ED visits for psychiatric emergencies were retrieved from the hospital database from 2002 to 2010. The total number of ED visits was 725,812 throughout the study period, 11,786 of which for emergency psychiatric problems. We found a strong seasonal distribution of emergency psychiatric visits, peaking in summer and at the beginning of spring. The linear regression analysis showed a strong positive association between number of daily emergency psychiatric visits and mean daily air temperature (R=0.82; P<0.001), and an inverse association with mean daily air humidity (R=-0.52; P<0.001). These findings suggest that psychiatric disorders follow a significant seasonal variation, so that it may be advisable to strengthen psychiatric emergency services during the hottest months.